2002
DOI: 10.1002/er.855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal storage on the performance of greenhouse

Abstract: SUMMARYIn this communication, thermal model of a greenhouse has been developed by incorporating the effect of water wall in the north side. Various temperatures, namely plant, water wall and room temperatures as a function of climatic and design parameters have been obtained by solving coupled single-order differential equation using Runge-Kutta method. Numerical methods have been carried out for a typical day of winter for Delhi condition. It has been observed that there is significant effect in the plant, ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The results revealed that the combined effect of a WWS with PCMs gave the best thermal performance over all other WWS arrangements considered. In 2003, Din et al [68] conducted a study on a WWS attached to a greenhouse to record the plant temperature, the water temperature, and the room temperatures for a day in the winter season by changing the factors such as absorptivity of the black colored WWS surface, water wall thickness, and the transmitted solar energy fraction. The results showed that a north facing WWS with a thickness of 27.5 cm could increase the room temperature by up to 4-5 • C at night and 3-4 • C in the daytime.…”
Section: Experimental Modeling Of Thermal Performance Of Wwsmentioning
confidence: 99%
“…The results revealed that the combined effect of a WWS with PCMs gave the best thermal performance over all other WWS arrangements considered. In 2003, Din et al [68] conducted a study on a WWS attached to a greenhouse to record the plant temperature, the water temperature, and the room temperatures for a day in the winter season by changing the factors such as absorptivity of the black colored WWS surface, water wall thickness, and the transmitted solar energy fraction. The results showed that a north facing WWS with a thickness of 27.5 cm could increase the room temperature by up to 4-5 • C at night and 3-4 • C in the daytime.…”
Section: Experimental Modeling Of Thermal Performance Of Wwsmentioning
confidence: 99%
“…Increasing the thermal capacity of the lower nodes throughout the year was not possible, and a constant crop density of 6 kg/m 2 has been utilized. The thermal properties of the crop are assumed to be similar to those of water . A sensible energy balance was carried out for the air in each thermal zone considering gains from surfaces of the zone, infiltration, ventilation, coupling air flows with adjacent zones and internal gains.…”
Section: Greenhouse Modelmentioning
confidence: 99%
“…Considerable research has been performed to reduce energy consumption for greenhouse heating. An effort has been made to study the effect of various greenhouse design parameters on the conservation of energy for environmental control using a mathematical model of a greenhouse thermal environment (Tiwari et al, 2002Din et al, 2003;Jain and Tiwari, 2003;K . o orner and Challa, 2003;Ghosal et al, 2004; .…”
Section: Introductionmentioning
confidence: 99%